WATER EXCTRACT OF PURPLE SWEET POTATO INCREASE SUPEROXIDE DISMUTASE, CATALASE GENES AND DECREASE MDA LEVEL IN MULTIPLE ORGANS OF DIABETIC WISTAR RATS - Bagus Komang Satriyasa; I Made Jawi (Journal of Global Pharma Technology, 2017)
Objective: The purpose of this study was to prove the water extract of purple sweet potatoes can increase superoxide dismutase (SOD) gene expression and catalase (CAT) and decrease malondialdehyde (MDA) in vital organs of diabetic rats. Method: This study was randomized experimental design with posttest only control group design. Sample divided into 2 groups: control and treatment groups, respectively 18 diabetic Wistar rats. The control group will be given streptozotocin. The treatment group was given streptozotocin and water extract of purple sweet potato 4 cc/day. This treatment is carried out for 2 months. Result: Water extract of purple sweet potato was proven significantly increased mRNA expression of aorta and kidney SOD but decreased SOD mRNA expression in the liver (p <0.05). This water extract also increases SOD mRNA expression in cardiac but not statistically significant (p> 0.05). Water extract of purple sweet potatoes also found significantly increased renal and cardiac expression of CAT mRNA (P <0.05), but not statistically significant (p> 0.05). Conclusion: Purple sweet potatoes extract to decrease the expression of liver CAT mRNA non-significantly, and decrease MDA in liver and kidney of diabetic Wistar rats significantly (P <0.05).